2D shear wave elastography combined with age and serum biomarkers prior to kasai surgery predicts native liver survival of biliary atresia infants. (4th June 2020) - Wang, G.; Chen, H.; Xie, X.; Cao, Q.; Liao, B.; Jiang, H.; Shan, Q.; Zhong, Z.; Zhou, W.; Zhou, L.
Abstract: Background: The prognosis of patients with biliary atresia (BA) after Kasai portoenterostomy (KPE) varies, and precisely predicting the outcomes of KPE before surgery is still challenging. Methods: A total of 158 patients who underwent KPE in our hospital were included in this study. The patients in the training cohort were recruited from January 2012 to October 2017 ( n  = 118), and then, those in the validation cohort were recruited from November 2017 to April 2019 ( n  = 40). Combined nomogram models were developed based on two‐dimensional shear wave elastography (2D SWE) values and other biomarkers. The utility of the proposed models was evaluated by C‐index. Results: 2D SWE played a potentially important role in predicting native liver survival (NLS) of BA patients with a C‐index of 0.69 (0.63 to 0.75) in the training cohort and 0.76 (0.67 to 0.85) in the validation cohort. The nomogram A based on 2D SWE values, age, gamma‐glutamyl transferase (GGT) and aspartate aminotransferase‐to‐platelet ratio (APRI) had a better C‐index in the training cohort [0.74 (0.68–0.80) vs. 0.66 (0.60–0.73), P  = 0.017] and in the validation cohort [0.78 (0.70–0.86) vs. 0.60 (0.49–0.71), P  = 0.002] than the nomogram B (without 2D SWE). Using risk score developed from nomogram A, we successfully predicted 88.0% (22/25) of patients in the training cohort and 75.0% (9/12) in the validation cohort to have survival time of less than 12 months after KPE. Conclusion: The combined nomogram model based on 2D SWE values, age, GGT and APRI prior to KPE can effectively predict NLS in BA infants. Abstract :